Workplace Empowerment and Librarianship: A Perception of Female Employees in Pakistan - Saleem, Qurat Ul Ain; Ameen, Kanwal (The new review of academic librarianship, 2024)
The aim of this study was to investigate the perception of female employees regarding workplace empowerment. The study also emphasized the alleged advantages of employee empowerment in the workplace and pinpointed the barriers to empowerment. This paper is based on qualitative data collected, through the semi-structured interview with female library professionals working in the higher education commission's recognized universities of Punjab- Pakistan, as a part of doctoral studies. According to the study, respondents most frequently defined "workplace empowerment" as having the freedom to do duties as they see fit. They also emphasized the benefits of workplace empowerment on both the personal and professional levels. Three categories-managerial, organizational, and individual factors-are used to categorize the obstacles cited by the participants. Although there is no study of this kind on the topic of workplace empowerment of female employees in the local context of Pakistan, this work adds significantly to the paucity of literature on the subject. This study is extracted from the Ph.D. thesis of the researcher. This study is limited in terms of its population as the data was collected from female library professionals in the Punjab province of Pakistan. The results may aid stakeholders and higher authorities in eradicating workplace empowerment concerns and in formulating evidence-based strategies or policies to enable women to execute their jobs more effectively. This qualitative study adds value to the literature by showing the actual situation of female employee empowerment in a developing country like Pakistan.